The Outcome of Keystone Flap for Lower Extremity Defects: A Systematic Review - Marcevianto, Kevin Varian; Wardhana, Aditya; Putri, Nandita Melati (Jurnal Plastik Rekonstruksi, 2024)
Introduction : Lower extremity defect poses a significant challenge in reconstructive surgery due to the limited usability of soft tissue. The keystone flap which utilizes fasciocutaneous perforators, has emerged to be a potential technique in fixing soft tissue defects. However, scientific evidence, specifically on its effectivity and complication rate in lower extremity defect is lacking. Therefore, this systematic review aims to assess the outcome and potential complications correlated to the use of Keystone Flap in repairing lower extremity defect. Method : This systematic review was done in accordance to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Literature searching was conducted using four databases, which is PubMed Central, Embase, Scopus and Cochrane Library. Result : A grand total of sixteen studies were included in the review. Among it, fourteen studies were case series. The others were cohort prospective and single arm interventional studies. Out of the 662 keystone flaps used, a total of 129 complications (19.5%,) were recorded, with the majority being infection or cellulitis (5%, n=33), delayed healing (4.5%, n=30), wound dehiscence (4.3%, n=28), and partial flap loss or necrosis (2%, n=13). Conclusion: The keystone flap could be an alternative for lower extremity defect with a realtively low complication rate.